SUBSURFACE SOIL CHARACTERISATION USING VERTICAL ELECTRICAL SOUNDING FOR SUPPORTING INFRASTRUCTURE DEVELOPMENT AT SYIAH KUALA UNIVERSITY - Amsir, Amsir; Masrurah, Zakia; Aflah, Nurul; Pramana, Agus Hari; Baramsyah, Haqul (Universitas Mataram, 2026)
This study characterises the subsurface soil properties in the western sector of Syiah Kuala University, specifically the Kopelma Darussalam area, using Vertical Electrical Sounding (VES) with a Schlumberger configuration. Nine measurement points were deployed to obtain resistivity profiles supporting infrastructure development planning. The results indicate that the surface layer (0–15 m) exhibits high resistivity (12.0–270.2 Ωm), suggesting dry sandy material with high permeability and sufficient bearing capacity. Below 15–30 m, resistivity decreases (1.9–26.5 Ωm), indicating a water-saturated layer potentially functioning as an aquifer, which has implications for soil stability. The deepest layers (>30 m) show low resistivity (<5 Ωm), reflecting low-permeability materials less suitable for heavy construction, though some high-resistivity anomalies suggest dense sandstone formations suitable for foundations. These findings provide preliminary geotechnical zoning insights, aiding developers in selecting appropriate foundation locations, improving construction safety, and ensuring long-term infrastructure stability at University Syiah Kuala.